2019
DOI: 10.1007/s00401-019-01970-9
|View full text |Cite
|
Sign up to set email alerts
|

Tau drives translational selectivity by interacting with ribosomal proteins

Abstract: There is a fundamental gap in understanding the consequences of tau–ribosome interactions. Tau oligomers and filaments hinder protein synthesis in vitro, and they associate strongly with ribosomes in vivo. Here, we investigated the consequences of tau interactions with ribosomes in transgenic mice, in cells, and in human brain tissues to identify tau as a direct modulator of ribosomal selectivity. First, we performed microarrays and nascent proteomics to measure changes in protein synthesis. Using regulatable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 60 publications
(100 reference statements)
11
96
0
Order By: Relevance
“…Interestingly, in Tau R406W flies we note an ~18% increase in agingassociated transcripts, with 7,970 genes affected (versus 6,742 in controls). However, within the proteome, the reverse pattern is seen with only 258 age-associated protein changes detected (versus 1,155 in controls), representing a 78% reduction, and potentially consistent with reports of Tau-induced translational dysregulation [40][41][42]. A similar trend for the proteome is observed in Tau WT animals; although, the magnitude of changes was more modest (Additional File 2: Table S3).…”
Section: Integrated Longitudinal Analysis Of Differentially Expressedsupporting
confidence: 84%
See 2 more Smart Citations
“…Interestingly, in Tau R406W flies we note an ~18% increase in agingassociated transcripts, with 7,970 genes affected (versus 6,742 in controls). However, within the proteome, the reverse pattern is seen with only 258 age-associated protein changes detected (versus 1,155 in controls), representing a 78% reduction, and potentially consistent with reports of Tau-induced translational dysregulation [40][41][42]. A similar trend for the proteome is observed in Tau WT animals; although, the magnitude of changes was more modest (Additional File 2: Table S3).…”
Section: Integrated Longitudinal Analysis Of Differentially Expressedsupporting
confidence: 84%
“…Though further investigation is warranted to confirm these observations, our analyses define Tau expression signatures in the both transcriptome and proteome enriched for genes implicated in translation, including numerous ribosomal proteins. Consistent with this, pathologic forms of Tau have been shown to avidly bind ribosomal proteins and disrupt their function [40][41][42].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…No significant change in GFP activity was observed in presence of equivalent amounts of the native BCAII protein. Earlier studies had also indicated that the tau protein might possess the ability to modulate the translation process 4,26 . Hence the translational suppression in presence of the tau protein variants implies that the loss of physical integrity of the ribosomal population (as observed by change in A 260 nm profile in Fig.…”
Section: Effect Of Tau On Eukaryotic Ribosomesmentioning
confidence: 99%
“…The ribosome and protein synthesis have been previously associated with mild cognitive impairment and AD (Ding et al, 2005;Hernández-Ortega et al, 2016;Langstrom et al, 1989;Sajdel-Sulkowska and Marotta, 1984) . Pathological tau has also been shown to determine translational selectivity and co-localize with ribosomes (Koren et al, 2019;Meier et al, 2016) . P. gingivalis DNA promotes aggregation of tau (Tetz et al, 2020) , and it has been postulated that tau fibrillization may block cytoskeleton-trafficking infections agents (Moir et al, 2018) .…”
Section: Discussionmentioning
confidence: 99%